Costa Rica : Financial Sector Assessment - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) summarizes the joint International Monetary Fund-World Bank Financial Sector Assessment Program (FSAP) report for Costa Rica, completed in August 2002, whose diagnosis and assessment, are based on information available as of end-2001. Costa Rica has a record of substantial output growth, with low macroeconomic volatility, but short term prospects remain uncertain. Thus, this stable macroeconomic environment masks some sources of tension, not least in respect of public sector debt, but also regarding the external accounts. Furthermore, the fiscal deficit widened during the l980s and 1990s, reflecting depressed tax revenues, and significant increases in pension expenditures. In contrast, the monetary and exchange rate regime that promotes dollarization, limits the scope for relative price adjustments, revealing an exchange rate that seeks to preserve external competitiveness, subject to the constraint of ensuring credibility of the crawling peg. Recommendations are set in light of the following considerations: leveling the playing field between public and private banks appears to be a key strategic priority. Therefore, regarding prudential oversight, most urgent are reforms to establish consolidated supervision of financial conglomerates, and strengthen the supervision of onshore banks, which would strengthen prudential oversight, limiting the financial system's exposure to systemic risk, particularly if the current monetary regime is maintained. With respect to the financial system safety net, it is essential that the planned introduction of a (limited) deposit insurance scheme be accompanied by strengthened supervision, and the establishment of a bank failure resolution framework. Reforms should ensure viable pension systems, and improve the functioning of securities, pensions, and insurance markets.